A Path With Heart. A Guide through the Perils and Promises of Spiritual Life. Jack Kornfield. - Solé-Leris, Amadeu (Buddhist Studies Review, 1997)
A Path With Heart. A Guide through the Perils and Promises of Spiritual Life. Jack Kornfield. Rider, London 1994 (1st ed. Bantam Books, New York 1993). xii, 352 pp. £12.99. ISBN 0-7126-7430-6.